Zinc transformations in a rice soil irrigated with sodic wafer - MINHAS, NEETU; CHHIBBA, I M (The Indian Journal of Agricultural Sciences, 2013)
Transformation of native and applied Zn in an alkaline calcareous loam soil transplanted with rice (Oryza sativaL.) and irrigated with water having varying levels of sodicity (RSC 0,5, 10 and 20 me/litre) was studied in a screenhouseexperiment. Of the various fractions, water soluble plus exchangeable Zn (WSE-Zn), amorphous oxides and carbonatesbound Zn (AMOX+CBT-Zn) and Zn bound by crystalline oxides (CRYOX-Zn) experienced an increase, whereas thecomplexed Zn (COM-Zn), organically bound Z11 (OO-Zn) and residual Zn (RES-Zn) registered a decrease with increasingwater sodicity irrespective of the sampling stage. Residual Zn (RES-Zn) formed the most dominant fraction of Zn. Allthe fractions appeared to be in a dynamic equilibrium as revealed by significant correlations among them.